2011
DOI: 10.1007/s10587-011-0031-0
|View full text |Cite
|
Sign up to set email alerts
|

Some algebraic properties of hypergraphs

Abstract: We consider Stanley-Reisner rings k[x 1 , . . . , xn]/I(H) where I(H) is the edge ideal associated to some particular classes of hypergraphs. For instance, we consider hypergraphs that are natural generalizations of graphs that are lines and cycles, and for these we compute the Betti numbers. We also generalize some known results about chordal graphs and study a weak form of shellability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…As mentioned in Example 4.8, there are clutters such that every subclutter contains a complete-neighborhood vertex, but that are not chordal. We can however use a similar technique to show that clutters with a complete-neighborhood vertex in every induced subclutter are vertex decomposable, improving the previous result [14,Theorem 4.3] that such clutters are shellable: Proposition 6.11. Let C be a d-uniform clutter such that every induced subclutter has a complete-neighborhood vertex.…”
Section: Alexander Duals Of Complements To Chordal Clutterssupporting
confidence: 55%
“…As mentioned in Example 4.8, there are clutters such that every subclutter contains a complete-neighborhood vertex, but that are not chordal. We can however use a similar technique to show that clutters with a complete-neighborhood vertex in every induced subclutter are vertex decomposable, improving the previous result [14,Theorem 4.3] that such clutters are shellable: Proposition 6.11. Let C be a d-uniform clutter such that every induced subclutter has a complete-neighborhood vertex.…”
Section: Alexander Duals Of Complements To Chordal Clutterssupporting
confidence: 55%
“…In particular, if C is a chordal clutter in Emtander's sense, then I C has a linear resolution over any field. In his later work, he showed that for a chordal clutter C, in fact, the ideal I C has linear quotients [8] while it is still an open question whether this is true for generalized chordal clutters as well.…”
Section: Claimmentioning
confidence: 99%
“…Let ∆ be a triangulation of the dunce hat with 8 vertices as shown in Figure 4, which is originally introduced by Zeeman [25]. Let C be the 5-uniform clutter C = C 8,5 \ F ∆ , where ∆ = [8] \ F : F ∈ F (∆) .…”
Section: Other Known Chordalities Another Notion Of Chordality Has Be...mentioning
confidence: 99%
“…What spoils things is the connectedness property for graphs. This property is central in the definition of graphical building set whereas for hypergraphs the notion of being connected may be defined in many different but equally natural ways (see [6] and [10] for examples). It is thus not clear how to approach the problem.…”
Section: About Being Chordal Triangulated Et Ceteramentioning
confidence: 99%